Rethinking Theological Anthropology From the Notion of Imago Trinitatis: Postcolonial and Feminist Insights - Martínez Cano, Silvia (Feminist theology, 2025)
The cultural changes of the twenty-first century invite us to rethink the notion of the human person in light of the concerns of contemporary societies. The criticism directed at the dual and patriarchal anthropological paradigm calls for a dialogue with other theological formulations that envision the human being through other theoretical and practical lenses. In this article, I will first describe the anthropological turn of the last two decades. I will then discuss this turn from the standpoint of some emerging anthropological categories suggested by feminist and postcolonial approaches. Finally, I will relate the categories under discussion to theological anthropology, delving into the notion of imago trinitatis as a key concept for contemporary understandings of the human person.